Mineralocorticoid Receptor Antagonism by Finerenone Attenuates Established Pulmonary Hypertension in Rats. Issue 10 (18th August 2022) - Tu, Ly; Thuillet, Raphaël; Perrot, Julie; Ottaviani, Mina; Ponsardin, Emy; Kolkhof, Peter; Humbert, Marc; Viengchareun, Say; Lombès, Marc; Guignabert, Christophe
Abstract : Background: We studied the ability of the nonsteroidal MR (mineralocorticoid receptor) antagonist finerenone to attenuate vascular remodeling and pulmonary hypertension using two complementary preclinical models (the monocrotaline and sugen/hypoxia rat models) of severe pulmonary hypertension. Methods: We first examined the distribution pattern of MR in the lungs of patients with pulmonary arterial hypertension (PAH) and in monocrotaline and sugen/hypoxia rat lungs. Subsequent studies were performed to explore the effect of MR inhibition on proliferation of pulmonary artery smooth muscle cells derived from patients with idiopathic PAH. To validate the functional importance of MR activation in the pulmonary vascular remodeling characteristic of pulmonary hypertension, mice overexpressing human MR (hMR+) were studied, and curative treatments with finerenone (1 mg/kg per day by gavage), started 2 weeks after monocrotaline injection or 5 weeks after Sugen injection were realized. Results: We demonstrated that MR is overexpressed in experimental and human PAH and that its inhibition following small interfering RNA-mediated MR silencing or finerenone treatment attenuates proliferation of pulmonary artery smooth muscle cells derived from patients with idiopathic PAH. In addition, we obtained evidence that hMR+ mice display increased right ventricular systolic pressure, right ventricular hypertrophy, and remodeling of pulmonary arterioles. Consistent with these observations, curative treatments with finerenone partially reversed established pulmonary hypertension, reducing total pulmonary vascular resistance and vascular remodeling. Finally, we found that continued finerenone treatment decreases inflammatory cell infiltration and vascular cell proliferation in monocrotaline and sugen/hypoxia rat lungs. Conclusions: Finerenone treatment appears to be a potential therapy for PAH worthy of investigation and evaluation for clinical use in conjunction with current PAH treatments.